The impact of short-term contract on employee’s quality of work life in hospitality industry in Jordan - Alrousan, Ahmad; Albdareen, Rokaya; AlOqaily, Ahmad Nader (International Journal of Innovative Research and Scientific Studies, 2025)
There have been many changes in work around the world, which have led to economic changes and increased global competition due to the emergence of modern and advanced technology, as well as international competition due to globalization. Many organizations use short-term contracts due to the high costs in the business world, which have affected employees' wages. This study aimed to examine the effect of short-term contracts and six unique attributes on employees' Quality of Work Life: Compensation, Working Conditions, Growth and Development Opportunities, Work-Life Balance, Social Integration, and Constitutionalism within Jordan's hospitality sector. SEM of 375 participants highlights that STCs make a stronger contribution to enhancing QoWL via Compensation and Quality of Work Life, while other dimensions reflect a low positive impact. The research also emphasizes that employers cannot entice workers away from financial and work-life incentive options with growth, inclusiveness, and fairness alone; for a holistic experience of short-term employment, both elements are needed. These insights help to piece together the puzzle concerning short-term job trends and implications for developing strategies in the hope of better Quality of Work Life outcomes specific to labor-intensive industries such as hospitality.